Losing My Religion: Spiritual Discouragement amongst Christian Therapists due to Spiritual Immaturity in Christian Clients - Porter, Steven L. (Journal of psychology and theology, 2017)
This paper addresses the spiritual discouragement and religious doubt that can arise in the Christian therapist who repeatedly experiences spiritual immaturity and crisis amongst his or her Christian clients. While Christians certainly aren't perfect, they often fall so far short of that ideal that one can reasonably wonder whether the Christian faith possesses resources that effectively bring about positive growth and change. We contend that witnessing repeated spiritual immaturity, failure, and related crises amongst Christian clients can bring about intrapersonal spiritual struggle for the Christian therapist of those clients. In response to this problem, a religious orienting system is proposed that includes both epistemological and theological features that aid the Christian therapist in navigating the disillusionment and disorientation that can occur from repeat exposure to spiritual immaturity amongst Christian clients.